(untitled) (Research, Society and Development, 2021)
Measles is an infectious viral disease transmitted from respiratory secretions and droplets, which can progress to serious complications. In 2018, a critical epidemiological character was evidenced in the State of Pará, especially in the Xingu Region and in the municipality of Prainha. The research aims to analyze the outbreak, the prevalence of measles and the epidemiological profile of those infected in these locations, between 2013 and 2020. In this way, a cross-sectional, descriptive and retrospective study of the measles cases reported on the information system platform was carried out. Notification Appeals. The sample value collected was composed of 52 suspected measles cases, in which a relative predominance was obtained in the female population, under 10 years old, mostly brown and living in urban areas. Half of the individuals with suspected infection required hospitalization, 28.8% of the patients had the result of confirming the diagnosis of measles and 61.5% progressed to cure the symptoms. In relation to confirmed cases, there is also a very low female superiority, with prevalence of infection among individuals under 10 years of age. From the results presented, it was possible to corroborate the need for an effective vaccination campaign to mitigate the disease.